An ergonomic intervention in operation of a rotary maize sheller - TIWARI, P S; PANDEY, M M; GITE, L P; SHRIVASTAVA, A K (The Indian Journal of Agricultural Sciences, 2014)
Research work on the ergonomics of bicycle, reported in literature, mainly deals with sports and rehabilitation activities. However, the use of pedal power for occupational work such as stationary farm operations has got scant attention in the past. Keeping these points into consideration a study was conducted at CIAE, Bhopal to optimise the design parameters for a pedal operated rotary device (dynapod), which could be used as an interface between human worker and any rotary type process machine. The developed dynapod was interfaced with a hand operated rotary maize sheller and the performance of the machine and drudgery reduction while operated in pedalling mode was quantified and compared with those of hand cranking mode. The results indicated a significant increase in output capacity of the machine (282.7 kg/h versus 144.42 kg/h) with a significant reduction in work pulses (Î”HR) during the operation of the machine (35 beats/min versus 59.4 beats/min) in pedalling mode using dynapod. It was concluded that the rotary maize sheller should be popularised along with the dynapod for its better adoptability by the farmers.